Analisis Unsur Visual dan Makna Ekspresif pada Karya Gambar Siswa Sekolah Dasar Bertema “Lingkungan Sekitarku” - Niken Ria Nastiti; Andaryani, Eka Titi; Setiawan, Deni (Universitas Palangka Raya, 2025)
This study aims to describe the application of visual elements and interpret the expressive meaning in elementary school students' artwork themed